2008
DOI: 10.1371/journal.pone.0003258
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Isoaspartate Methyltransferase Prevents Apoptosis Induced by Oxidative Stress in Endothelial Cells: Role of Bcl-Xl Deamidation and Methylation

Abstract: BackgroundNatural proteins undergo in vivo spontaneous post-biosynthetic deamidation of specific asparagine residues with isoaspartyl formation. Deamidated-isomerized molecules are both structurally and functionally altered. The enzyme isoaspartyl protein carboxyl-O-methyltransferase (PCMT; EC 2.1.1.77) has peculiar substrate specificity towards these deamidated proteins. It catalyzes methyl esterification of the free α-carboxyl group at the isoaspartyl site, thus initiating the repair of these abnormal protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 43 publications
3
42
1
1
Order By: Relevance
“…3E). The oxidative stress is considered to be a favorable condition for Bcl-xL deamidation by a mechanism that is not dependent on the increased NHE-1 activity [26]. However, in our study, no significant increase of the ROS levels was induced by any of the drugs.…”
Section: Expression and Post-translational Modification Of The Bcl-xlcontrasting
confidence: 72%
“…3E). The oxidative stress is considered to be a favorable condition for Bcl-xL deamidation by a mechanism that is not dependent on the increased NHE-1 activity [26]. However, in our study, no significant increase of the ROS levels was induced by any of the drugs.…”
Section: Expression and Post-translational Modification Of The Bcl-xlcontrasting
confidence: 72%
“…This was accomplished by using a purification protocol that employed a resin linked to human recombinant PCMT1, which can only recognize isomerized proteins but not the one carrying normal aspartyl (27). These latter experiments provided the first evidence that Bcl xL undergoes deamidation under cell stress conditions, yielding its isomerized derivative, which is devoid of antiapoptotic function.…”
Section: Discussionmentioning
confidence: 99%
“…The overall scenario may be even more complex, because of the pleiotropic activity of this microRNA cluster on a number of other antiapoptotic genes (23, 28 -30, 35-37, 44), not just PCMT1 and also because other PCMT1 substrates, such as Hsp70, Hsp90, are involved in apoptosis (27), and both of these aspects may further complicate this model and certainly deserve further investigations. These results, as a whole, support a novel interpretation that PCMT1 should not be simply interpreted as a repair methyltransferase of aged/damaged proteins, but it may act as an effective modulator of apoptotic cell death, whose derangement may play a role in proliferative or degenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JAB1 could compete with Bcl-XL/Bcl-2 to bind to BclGs and thus promote apoptosis. Cimmino et al [60] found that cells overexpressing "wild-type" human isoaspartyl protein carboxyl-O-methyltransferase (PCMT) were resistant to apoptosis, whereas overexpression of antisense PCMT induced high sensitivity to apoptosis, even at low H 2 O 2 concentrations. By incubating the purified human recombinant PCMT with cell lysate, they identified that Bcl-xL was a specific methyl-accepting substrate of PCMT and thus lost its anti-apoptotic activity for the methylation modification.…”
Section: Tumor Suppressors and Oncogenesmentioning
confidence: 99%